Laboratórios de ciências/biologia nas escolas públicas do estado do Ceará (1997-2017): realizações e desafios - Mota, Maria Danielle Araújo (2019)
This PhD research deals with the articulation between the implantation and the development of the Science Laboratories in the public schools of the State of Ceará, as well as the implications of this educational policy for the teaching action of the teachers who work in the Sciences/Biology Laboratories. The study is of a qualitative nature, identified as a case study and is chosen as a general objective to analyze the implantation and development of the Science Laboratories in the public schools of the State of Ceará from 1997 to 2017, as well as their implications at the present time. These are the specific objectives: to analyze the legal documents that regulate the implantation and development of the Science Laboratories in the public schools of the State of Ceará; identify the accomplishment of the Laboratory and its articulation with the Teaching of Sciences/Biology; to discuss the relations established between the Education Department of the State of Ceará and the schools of Basic Education within the articulation theory and practice. In order to reach the objectives, the investigative process started with the following question: how was the implantation and development of the Science Laboratories in the public schools of the State of Ceará between 1997 and? The information, obtained through observations and individual interviews, was analyzed according to the guidelines of the Discursive Textual Analysis - ATD. Five (5) teachers who were involved in the implantation of the Laboratories and 6 (six) teachers currently in the Laboratories participated in the three schools surveyed. After analysis of documents and the subjects' narratives, it was verified that the implementation of the Laboratories took place in the period 1997-2000, with the participation of SECITECE, SEDUC and professors in the area of Sciences/Biology, and was marked by financial and but it was possible to complete the purchase of materials and training for teachers in the State of Ceará through the CVT and installation of Laboratories in the Lyceums. During the development period, from 2001 to 2007, policies made possible the revitalization and construction of new Laboratories - financial resources and the Ordinances that organized the teaching staff - demonstrating the importance of school management in monitoring the actions of the teacher in the Science/Biology Laboratory. However, when analyzing the period 2008-2017, named current, it was found that, although there is the Teacher Loan Ordinance, space and time in school, the use of the Laboratory of Sciences/Biology is timely for many of the subjects. It was concluded that the managers of these schools had a fundamental role in the pedagogical monitoring and monitoring of the activities carried out, since they can contribute with the teaching action in the Laboratory, because, through the pedagogical plans, the teachers are motivated to carry out activities and the involve other teachers, thus strengthening the teaching of Science and Biology in Basic Education. The thesis argues that there are subsidies for the understanding of the potentials and limits of Science/Biology Laboratories as environments for students to participate, share and experience practices, and that school management believes that it is possible to improve teaching and learning processes. learning, motivating the teachers, through continuing education, to re-signify the space of the Science/Biology Laboratory in the school.